(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
The multilateral trading system of the future is likely to continue to feel the pressure of protectionist pressures. However, as brought out trade protectionism would be a recipe for disaster. Nevertheless, continued support for more open trade will require other forms of protection, in the form of better social safety nets for the affected improved trade and economic infrastructure, supportiv domestic policies, etc. on these issues WTO has little control and these are of domestic policy mix to make trade opening indisputably acceptable.The multilateral trading system of the future will also have to take better account of the growing importance of global value chains. The geographical fragmentation of the value chain is leading to a structural change in international trade with more and more goods being made across a number of countries. The concepts such as "country of origin" or "resident versus non-resident’’ are losing relevance in international economics. The context calls for measurement of trade flows based on value added, which will indicate the domestic content of export, after subtracting direct and indirect imported inputs. Having the right tools to measure trade flows is essential in order to have a proper domestic debate about trade. Global value chains also require taking a closer look behind border rules and regulations. ·As riffs are gradually reduced either unilaterally or by virtue of the numerous preferential/ regional trade agreements being concluded, divergences in domestic regulatory frameworks require greater attention.